Exploration and Morphological Characterization of Aren (Arenga pinnata Merr) Plants in Luhak District, 50 Kota Regency - Dede Suhendra; Nike Karjunita; Wulan Kumala Sari (JERAMI : Indonesian Journal of Crop Science, 2023)
Aren palm (Arenga pinnata Merr) belongs to the palm tribe. The problem that is often encountered in aren palm plants is the low productivity of aren palm plants, this is allegedly because the seeds used are not superior seeds and cultivation techniques that are not yet appropriate. The low production of plants is thought to be due to the low knowledge of the community on the use of superior aren palm planting materials, where the cultivated aren palm is not considered superior properties, including the diversity of aren palm species that grow wildly is still high in one forest land, unclear identity of seeds used by farmers. Exploration is the first step in finding germplasm of aren palm plants that have the expected traits through breeding programs so that it is expected to be one of the solutions for the development of aren palm plants. This research will be conducted from May to October 2023 in community-owned aren palm plantations in 50 cities. The purpose of this research is to characterize the morphology of Aren plants in District 50 Kota and to see the level of diversity of aren palm plants in the area. The research method was survey method, with purposive sampling. The data collection technique is to observe the morphological parts of the plant in each sample. The data obtained were analyzed descriptively, while for the analysis of similarity the calculation of the NTSYS Ver 2.02 program was used. The results of the study obtained 4 clusters of palm plants from 3 villages namely Nagari Sungai Kamuyang, Sikabu-kabu and Mungo. Researchers obtained 15 samples of aren palm plants characterized by 19 characters, namely 10 characters have wide variability and 9 characters have narrow variability with a level of diversity ranging from 14% - 47%.